The effect of project approach-based science education program on problem-solving skills of preschool children. - Güley, Burcu; Keskinkılıç, Ayşegül (Humanities & Social Sciences Communications, 2024)
In this study, the effect of project approach-based science "education program on problem-solving skills" of preschool children attending a kindergarten was investigated. The study was conducted with a quasi-experimental design with pretest and posttest control group at a kindergarten affiliated with the "Ministry of National Education" located in a province in Turkey. The study sample consisted of 70 children (35 in the experimental group, 35 in the control group). The study data were collected through Personal Information Form and Age 4–7 "PSSS". While the Project Approach-Based Science Education Program (PABSEP) was applied to the children in the experimental group in 28 sessions for three days a week for 10 weeks in addition to the National Education Program, the National Education Program was continued in the control group. As a result of the analyses of the data obtained, significant differences were determined between the "PS" scores of the two groups in favor of the experimental group following the education programs applied (p < 0.05). It was concluded that the PABSEP positively affected the problem-solving skills of the preschool children, and that this effect was permanent (p < 0.05).